Nanotechnologies in the fight against coronaviruses - Szunerits, Sabine (Henry Stewart Talks, 2020)
The use of nanotechnologies in antiviral strategies, drugs, vaccines, and diagnostic tools, Using nanotechnologies against human coronaviruses including SARS-CoV-2, Specific benefits of using nanotechnologies, Carbon quantum dots